A study on customers' satisfaction towards Tabung Haji by using service quality dimension / Zahrul Hisyam Jefrry - Jefrry, Zahrul Hisyam (Faculty of Business Management, 2015)
This study is emphasis on the importance of service quality that has been offered by an organization. Service quality is an important element that will affect the customer satisfaction. The purpose of this paper is to test identify which are service quality dimension that influences the customer satisfaction towards Tabung Haji. A structured questionnaire was used to elicit response from consumers using a convenience sampling technique. A total of 100 responses were received. Needless to say, this study extends customer satisfaction towards Tabung Haji by using service quality dimension. Tangibility and empathy were found to be positively related to customer satisfaction, with empathy being the more influential. The study contains a limited number of measures in the model. Nevertheless, it provides new information on the emerging issue of service quality. Moreover, the result will be primarily beneficial to institution that offering service in Malaysia by offering an insight into the customer satisfaction towards Tabung Haji by using service quality dimension